Pro-atrial natriuretic peptide (pro-ANP) level in patients with severe sepsis and septic shock: prognostic and diagnostic significance - Lipinska-Gediga, M. (Springer-Verlag, 2012)
BACKGROUND: To establish the prognostic and discriminative value of the pro-atrial natriuretic peptide (pro-ANP) level in patients with severe sepsis or septic shock. PATIENTS AND METHODS: An observational and prospective study was conducted on 50 critically ill patients with severe sepsis or septic shock. Measurements of the level of procalcitonin (PCT) and mid-regional pro-ANP were determined in the serum of patients with commercially available immunoluminometric tests. RESULTS: The median pro-ANP level was significantly higher in non-survivors than in survivors (P < 0.05) on all consecutive days. No significant differences in the pro-ANP levels were observed in patients with severe sepsis and septic shock. There was a strong correlation between the PCT and pro-ANP levels on admission in non-survivors and in septic shock patients (r = 0.56, P = 0.007 and r = 0.43, P = 0.02, respectively). CONCLUSIONS: pro-ANP evaluated in severe sepsis and septic shock patients is a valuable prognostic biomarker, but, in contrast to PCT, which is routinely used as a diagnostic marker of severe sepsis and septic shock, it does not possess diagnostic and discriminative value.